Carbon sequestering ability and mineralizability of organic matter of different soils of Belarus - Tsybulka, Mikalai M. (Journal of the Belarusian State University. Ecology, 2019)
In the active pool of organic matter, the mineralizable fraction is easily 24.3–49.1 %, and it is difficult to mineralize – 50.9–76.0 %. There is a decrease in its value with increasing erosion degradation of soils. The mineralization capacity of peat soils is lower than that of sod-podzolic soils, in which the share of potentially mineralized carbon in the total organic matter is only 1.7 %. The carbon-sequestering capacity of sod-podzolic soils varies within the limits of 14.7–20.5, peat soils – 58.2–60.1. The organic matter of non-eroded soils is more stable compared to soils subject to erosive degradation.